Elbow Dislocations: A Review Ranging from Soft Tissue Injuries to Complex Elbow Fracture Dislocations - Carsten Englert; Johannes Zellner; Michael Koller; Michael Nerlich; Andreas Lenich (Advances in Orthopedics)
This review on elbow dislocations describes ligament and bone injuries as well as the typical injury mechanisms and the main classifications of elbow dislocations. Current treatment concepts of simple, that is, stable, or complex unstable elbow dislocations are outlined by means of case reports. Special emphasis is put on injuries to the medial ulnar collateral ligament (MUCL) and on posttraumatic elbow stiffness.